A re-evaluation of five European species of Spilomena with a key to European species and relevance to the fauna of North Europe, especially Finland (Hymenoptera: Pemphredonidae) - Vikberg, Veli (Entomologica Fennica, 2000)
A critical examination, including the study of type material, resulted in the following taxonomical changes in the sphecid wasp genus Spilomena: S. pulawskii Dollfuss, 1983 is synonymized with S. curruca (Dahlbom, 1843). Spilomena differens Blüthgen, 1953 is considered a valid species. S. exspectata Valkeila, 1957 is synonymized with Spilomena beata Blüthgen, 1953. Spilomena valkeilai sp. n. is described from southern Finland, Sweden and Norway. The value of the head form as a taxonomic character in Spilomena is pointed out. A key to species of Spilomena of Europe and the Canary Islands is presented. Spilomena beata and S. enslini Bliithgen are added to the fauna of Norway. Notes on the distribution of the species in North Europe, especially Finland are given.